2018
DOI: 10.1186/s13019-018-0810-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of anterior chest wall: a clinical analysis

Abstract: ObjectiveTo investigate the methods and clinical efficacy of reconstruction of chest defects with titanium sternal fixation system after the surgical resection of sternal tumors.MethodsA total of 6 patients with sternal tumor who were diagnosed and underwent resection and repair of the chest wall defects by titanium plates system, from 2017.3 to 2017.11 in our hospital were reviewed. Their pathological types, surgical reconstruction methods, follow-up results were analyzed.ResultsSix cases of sternal tumor wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Several studies have demonstrated various chest wall reconstruction methods in the fields of cardiac and thoracic surgery. Gao et al [ 13 ] reported on the use of titanium sternal fixation systems for reconstruction, while Ma et al [ 4 ] performed sternal reconstruction with 3-dimensional (3D) custom-made prostheses. Metal prosthesis carries the advantage of establishing adequate chest wall stability, but there are some limitations regarding the use of metal prosthesis including prosthesis dislocation, infection, or inappropriate sizing.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated various chest wall reconstruction methods in the fields of cardiac and thoracic surgery. Gao et al [ 13 ] reported on the use of titanium sternal fixation systems for reconstruction, while Ma et al [ 4 ] performed sternal reconstruction with 3-dimensional (3D) custom-made prostheses. Metal prosthesis carries the advantage of establishing adequate chest wall stability, but there are some limitations regarding the use of metal prosthesis including prosthesis dislocation, infection, or inappropriate sizing.…”
Section: Discussionmentioning
confidence: 99%
“…However, to reconstruct the sternocostal framework, the use of synthetic materials and implants comes to the fore. Biomaterials most often applied for these purposes are meshes and sheets made of vicryl, mersilene, teflon, polycaproamide, polypropylene, polytetrafluoroethylene, titanium, stainless steel, or combinations thereof [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Noted disadvantages of these implants include secondary wound infections in up to 6% of cases [ 18 ], inadequate thoracic cage rigidity, respiratory dysfunction, and seroma, which often leads to revision surgery and the removal of an inconsistent device.…”
Section: Introductionmentioning
confidence: 99%
“…Noted disadvantages of these implants include secondary wound infections in up to 6% of cases [ 18 ], inadequate thoracic cage rigidity, respiratory dysfunction, and seroma, which often leads to revision surgery and the removal of an inconsistent device. There are published reports on the use of sternal and costal endografts made from fluorine- or carbon-containing materials, and of vascular grafts [ 12 , 13 ]. The concerns typically encountered when considering these surgical procedures are related to late complications, side effects, and inadequate follow-up and physical rehabilitation, stemming from the incomplete restoration of the framework of the thoracic cage.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid respiratory dysfunction, rigid reconstruction is necessary after resection of a sternum tumor [ 1 ]. Indeed, titanium plates have been widely used for this purpose [ 2 , 3 ] because titanium plates are biocompatible [ 4 ] and can be shaped to fit thoracic defects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%